SENGKETA PEMILIHAN KEPALA DESA DAN PENYELESAIANNYA DITINJAU MENURUT UU RI NO, 32 TAHUN 2004 JO. UU RI NO, 12 TAHUN 2008 - Joni Pikal (Universitas 17 Agustus 1945 Samarinda, 2015)
ABSTRACT In raised the issue of implementation: DISPUTE ELECTION VILLAGE HEAD and solutions IN REVIEW BY LAW - SHRIMP IN 2004 JO NO 32 OF LAW NO 12 YEAR 2008 MAS MOUNTAIN DISTRICT CENTRAL KALIMANTAN background of this research problem. disputes exclusive village elections as a legislative body at the level of desa.dapat at say a power struggle, it can be seen why this could happen dispute pepilihan village head, the clash between the two groups that each have the right and obligation, in the organization of village elections less supervision and the actions of the local government, the purpose of this study is to describe the procedures for implementing the government's stewardship of the village which has a duty, obligation and authority. in the process of political reform demanded that local elections should be honest, fair, and clean. without any element of corruption. In this research using empirical juridical methods, field research and interviews as well as where to collect legal material which is then processed and analyzed literature. while the research subjects are disputed election of village heads and completion, the results of this study explain what happened on the ground that the implementation of the conflict basically have various elements that there are two parties involved the objectives made in the target, actions and circumstances which gave birth to a conflict. and factors - factors for the sake of political interests compete for power. rather than the nature of that desired by the village government Pilkades is an honest, fair, clean and free from collusion, corruption, and nipotisme. Regulation walking areas less than optimal, in the implementation of the democratic party there are many problems and issues as early symptoms Pilkades conflict that marred violent unrest that could undermine the integrity and existence of the knowledge society. post Pilkades disputes in some districts or villages the absence of clear rules need to be clear rules of the governor or regent. So that in implementing the decisions required honesty jointly carried unanimously, so bermamfaat for the benefit peopple many, poured in principle to the 4 is a democracy led by the inner wisdom of deliberations of representatives, and (NKRI in indonesian) as the unitary state of Indonesia so that subsequent disputes Pilkades not reoccur any area.